Food safety behavior of food handlers in the kitchen of a 5-star hotel in Bangkok: A case study of interns - Dangkhaw, Nantida; Smith, Natnaree; Langprasert, Supunsa (Journal of Behavioral Science for Development, 2022)
The aims of this study were (1) to study food sanitation behavior, (2) to study food sanitation behavior factors, and (3) to study the relationship of factors affecting food sanitation behavior for food safety. The questionnaire was used and answered by 217 food handlers who are interns in food management related programs. The result showed that the majority of food handlers had knowledge of food sanitation, especially what should be done or must be done to keep food safe and were encouraged by a command or a role model of their supervisors. The majority of food handlers had the strongly responsible attitude towards adhering to overall food sanitation practices. A positive correlation was found between the factors of knowledge, social support, and attitude of food handlers and the behavior of food sanitation at the hotels. From a multiple regression analysis, it was found that the attitude factor affected the behavior of food handlers the most, followed by knowledge and social support, respectively, at a predictive ability of 43.7%. As such, if the hotel operators or the educational institutions desire to develop the potential of food handlers, they should first promote a positive attitude towards food sanitation, and then provide the food handlers with regular training or education sessions on food sanitation as needed for their functional levels. Moreover, the hotel operators should have in place a food safety policy and relevant facilities to accommodate more efficiency of work performance.